SUBMARINE GROUNDWATER DISCHARGE MEASUREMENT ON THE SANDY UNCONFINED AQUIFER AT THE CARNAVAL BEACH, ANCOL (JAKARTA BAY) - Bakti, Hendra; Lubis, Rachmat Fajar; Delinom, Robert M.; Taniguchi, Makoto (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2016)
Submarine groundwater discharge (SGD) is defined as all direct discharge of subsurface fluids into coastal zone. Components of SGD consist of fresh submarine groundwater discharge and the recirculated saline seawater discharge. SGD could act as a pathway for the transport of anthropogenic contaminants and nutrients to coastal waters. Measurement SGD at Carnaval Beach, Ancol, Jakarta was focussed on unconfined groundwater system. The method of quantified used automatic seepage meter for measured of SGD and installed conductivity temperature depth. The average SGD rate was 0.21 mm/min on March 20-31, 2009 consist of 19.05% fresh water, 80.95% recirculated seawater. April 1-23, 2009, the average SGD rate was 0.81 ml/min which consisted of 16.04% fresh water, 83.96% recirculated seawater. SGD fluctuation was opposite with the tide. As a result, submarine groundwater discharge at Jakarta coastal area was defined and can be measured to quantify.